Análise do envolvimento de proteínas do látex de Calotropis procera na defesa vegetal face a estresses biótico e abiótico - Souza, Isabel Cristina da Costa (2019)
ABSTRACT Throughout evolution, the plants have been developing defense mechanisms for their protection, an example of this is the production of latex as a vegetal resource in the defense against herbivores and phytopathogens. The chemical and functional diversity of the laticiferous fluids is being studied, with emphasis on secondary metabolites and defense proteins. The species Calotropis procera belongs to the family Apocynaceae and is prominent in latex production. Three classes of proteins isolated from latex: proteases, osmotin and chitinases. However, the objective of this study was to trace a relationship between the proteins present in the latex of C. procera and their role in plant defense against biotic and abiotic stresses. For this, methodologies for the in vitro control of the mycelial growth and germination of the phytopathogenic fungi Colletotrichum gloeosporioides, Fusarium tupiense e F. oxysporum f. sp. cubense testing the synergistic effect of total proteins and their isolated fractions. Thus, it was verified the total proteins present a greater effect when compared to the latex fractions of C. procera, but the combination of the proteases with the osmotin enhaces the effect compared to the isolated osmotin. The total proteins of C. procera latex were tested as elicitors in the defense of banana seedlings challenged with the fungus F. oxysporum f. sp. cubense. It was observed that plants who were previously treated with latex proteins showed a reduction in the occurrence and severity of the disease, maintenance of growth, reduction in membrane damage and increase in the activity of the antioxidant system enzymes. Osmotins are defense-related proteins when it comes to biotic and abiotic stresses. To test this hypothesis to the sequence of the process of Nicotiana tabacum with the osmotin of C. procera (CpOsm). After confirming the transformation of the first generation of plants, the total proteins of tobacco leaves were extracted and tested in the inhibition of the germination and mycelial growth of the fungi F. tupienses and F. oxysporum f. sp. cubense. The results show plants transformed with the CpOsm gene inhibit the mycelial growth of phytopathogenic fungi with greater efficiency when compared to the untransformed plants. The transformed and control plants were submitted to salinity resistance test. For this, the plants were maintained in nutrient medium MS with 300 mM NaCl for seven days, after the transformed plants had no difference in growth and number of leaves, however they were able to increase the concentration of free proline when compared to the non-plants transformed. It is possible to measure a probable effect of C. procera latex proteins on the plant defense mechanism against the attack of phytopathogens and to relate the CpOsm protein with mechanisms of action of protection of plants to saline stress and attacks by phytopathogens.